Proposta de ciclos: estudo sobre a Escola Sarã de Cuiabá-MT, à luz das políticas públicas de inclusão - Tavares, Arlete de Fátima (2010)
This paper has the objective of studying and understanding the Cycles Approach; verifying whether this approach contributes or not to the effectiveness of the public policies on inclusion, to the improvement of the learning process and to the creation of a gathering room for learning. The interest in the subject matter was born out of the researcher professional experience at the state-owned schools network, in the city of São Paulo-SP, from 1988 to 2000, and later in the city of Cuiabá-MT, from 2004 to 2006. The problems: discomfort experienced by the researcher, caused by the introduction of the Cycles, without having the teachers previously questioned about it or without receiving satisfactory instruction to work on this approach. A number of illiterate students unable neither to solve basic Maths operations nor problem-solving situations in both third and fourth grade (Elementary School). Hypothesis: if the Cycles Approach was well introduced, it could contribute not only to the improvement of the learning process, but also to the constitution of a gathering room where both teacher and student would voluntarily support this approach and, also, it could contemplate the teaching-learning process in a satisfactory manner. Theoretical references: Azanha (2004); Teixeira (1957); Caseiro (2000); Silva (2000; 2006; 2007; 2008), Meneses (2004) among others. Object of study: Escola Sarã de Cuiabá (School). Methodology: it was adopted the qualitative research and, as methodological procedure, documental/bibliographic research and study of the case. The cycles of learning cannot be seen as concluded. The introduction itself is not enough. They must be analyzed, questioned and reformulated, if necessary. To achieve this, it is important to listen to teachers, parents, students, with their suggestions and proposals. It is also fundamental to have the system of education evaluating the students, with the aim of identifying what the advances and aspects are which present difficulties to the reformulation of the Cycles Approach